Loss of Capsule in Streptococcus suis - Meekhanon, Nattakan (Journal of Mahanakorn Veterinary Medicine, 2016)
Streptococcus (S.) suis is an important zoonotic pathogen. It can cause various diseases, particularly meningitis in swine and human. Most patients recovering from meningitis further develop permanent deaf. Among the proposed virulence factors described so far, capsule is thought to be a significant factor contributing to severe diseases. According to the antigenicity of the capsular polysaccharides, S. suis can be classified into different serotypes. However, the nontypeable S. suis has increasingly been reported. The loss of capsule in S. suis, which results in being the nontypeable strain, can be caused by the alteration of gene(s) in a group of capsular polysaccharide synthesis genes. In addition, the non-encapsulated cells were reported to have greater adherence and biofilm formation abilities than those of the encapsulated cells. Since the adherence to host cell has been considered as the initial step for the pathogenesis of S. suis infection, the loss of capsule in S. suis may play an important role in the severe infection in both swine and human.